2015
DOI: 10.1111/sjop.12207
|View full text |Cite
|
Sign up to set email alerts
|

Suicide attempts and stressful life events among female victims of intimate partner violence living in poverty in Nicaragua

Abstract: This article describes a study of 136 female intimate partner violence victims living in poverty in Nicaragua. The paper aimed to analyze the relationship between experiencing stressful life events (SLE) and perceived social support with suicide attempts, and to evaluate the differences in the SLE experienced by female suicide attempters versus non-attempters. The results showed the existence of a high level of SLE among the interviewees, and that women who have attempted suicide have experienced substantially… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
47
1
3

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 33 publications
(55 citation statements)
references
References 70 publications
4
47
1
3
Order By: Relevance
“…These percentages reflect the prevalence of the problem that is higher than that found by Afifi et al (). However, it does seem to be consistent with the findings of previous research, according to which suffering from experiences related to victimization as a child are related to suicide attempts (Afifi et al, ; Devries et al, ; Guillén et al, ), and for which a higher probability of suicide attempts has also been observed. The results also appear to indicate a correlation between suffering from child abuse and mistreatment and other forms of violence in adulthood among the sample of Nicaraguan women.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…These percentages reflect the prevalence of the problem that is higher than that found by Afifi et al (). However, it does seem to be consistent with the findings of previous research, according to which suffering from experiences related to victimization as a child are related to suicide attempts (Afifi et al, ; Devries et al, ; Guillén et al, ), and for which a higher probability of suicide attempts has also been observed. The results also appear to indicate a correlation between suffering from child abuse and mistreatment and other forms of violence in adulthood among the sample of Nicaraguan women.…”
Section: Discussionsupporting
confidence: 91%
“…Although the studies that examine the concurrence between child abuse, suffering from other types of abuse, and the consequences for mental health in adulthood are limited (Turner, Taillieu, Cheung, & Afifi, ). Some research have shown that witnessing violence towards their mother and having suffered from physical violence and sexual abuse in childhood are important factors affecting the health of women, which increase the risk of suicide attempts among victims of violence (Afifi et al, ; Devries et al, ; Guillén, Panadero, Rivas, & Vázquez, ). Polyvictimization, a recent concept that includes multiple acts of violence (intimate partner violence, family violence, and community violence; Hamby & Grych, ) is related to suicidal behavior, especially among women (Soler, Segura, Kirchner, & Forns, ).…”
Section: Introductionmentioning
confidence: 99%
“…The SLEs suffered by homeless people in Leon were quantitatively more numerous, qualitatively more severe, and occurred at younger ages than nonexcluded groups in different regions of Nicaragua (Vázquez et al., ) or the city of León (Guillén et al., ; Vázquez et al., , ). However, the sample suffered from SLEs in a similar manner to other socially excluded groups in the city of León, such as trash pickers (Vázquez, in press), who are mainly subject to processes of chronification of a situation of social exclusion, with pseudoinheritance from parents to children (Vázquez, ; Vázquez & Panadero, ).…”
Section: Discussionmentioning
confidence: 99%
“…Other than increasing vulnerability to HIV infection (Ulibarri et al, 2010), unwanted pregnancy (Silverman, Gupta, Decker, Kapur, & Raj, 2007), and physical injury (Antai, 2011), violence often causes adverse health consequences, including mental health problems (e.g., depression, loneliness, and suicidal behavior) among FSWs (Hong, Zhang, Li, Liu, & Zhou, 2013; O’Campo, Woods, Jones, Dienemann, & Campbell, 2006; Ouellet-Morin et al, 2015). Women victims of partner violence often experience loneliness (Rokach, 2007) and suicide attempts (Guillen, Panadero, Rivas, & Vazquez, 2015). Loneliness occurs often across all psychotic disorders (Badcock et al, 2015).…”
Section: Introductionmentioning
confidence: 99%